Unsur-unsur retorik dalam puisi Melayu Al-Amin karya A.Samad Said = Rhetorical Elements in the Malay Poetry Al-Amin by A. Samad Said - Ahmad H.Osman, Rahmah; Nasir, Mohd Sharizal (Division of Usuluddin, Academy of Islamic Studies, University of Malaya, 2013)
This article analyses a product of the Islamic literature namely the poem Al-Amin by A. Samad Said which presents the story of Prophet Muhammad’s (p.b.u.h.) life. It also observes the emergence and development of the discourse of the Islamic literature in Malaysia, in order to highlight the conceptual thinking underlying this discourse by studying Al-Amin as an example. This article applies several Malay and Arabic rhetorical theories to analyses the linguistic value of Al-Amin. It also quotes several verses from Al-Amin to show the utilisation of such theories. Finally, this article finds that Al-Amin contains various esthetical values such as anaphora, assonance, alliteration, prosaic, imagination, preposition, listing of names, tashbīh, uslūb al-istifhām, waṣf al-ṭabī‘ah, tikrār and iqtibās. This directly indicates that Al-Amin is a product of the Islamic literature.